Negara dalam Pemikiran Politik (Analisis dengan Pendekatan Siyasah Syar'iyah) - Usman Jafar (Al-Hikmah Journal for Religious Studies, 2011)
The term of state in some experts has various definition. This   cannot be avoided because of different thought in understanding the term. The different of environment in which they live, the different of social politic, and the belief of religion are the factors influencing the thought. The difference, thus also would add more knowledge to our insight because it will complete and perfect each other. On the other side, someone can disagree with this term, but he must agree to  require the state, because the state represent the politic instrument to implement the unity and welfare in living together. The function of state in management of government should be rised namely the function of application in governmental statute.  The people in this case are to get  the right of authority to apply the function of government.  The way of thought can  understand  the ideal government that is the government that can understand the desire and aspiration of community